Literature and the War on Terror : nation, democracy and liberalisation - Ali, Sk. Sagir (London ; New York : Routledge, 2023)
"This book examines cultural imaginations post 9/11. It explores the idea of a religious community and its multifaceted representations in literature and popular culture. The essays in the volume focus on the role of literature, film, music, television shows and other cultural forms in opening up spaces for complex reflections on identities and cultures, and how they enable us to rethink the 'trauma of familiarity', post-traumatic heterotopias, religious extremism, and the idea of the 'neighbor' in post-9/11 literary and cultural imagination. The volume also probes the intersections of religion, popular media, televised simulacrum, digital martyrdom in the wake of 9/11. It also probes the simulation of new age media images with reference to the creation and dissemination of 'martyrs', the languages of grief, religionization of terrorism, islamophobia, religious stereotypes, and the reading of comics in writing the terror. An essential read, the book reclaims and reinterprets the alternative to a Eurocentric/Americentric understanding of cultural and geopolitical structures of global designs. It will be of great interest to researchers of literature and culture studies, media studies, politics, film studies, and South Asian studies"--
Introduction: Surveying the frontiers of home, democracy and belonging in the literature of war on terror / Sk Sagir Ali -- Cartographies of otherness and strategic outsiderism in post 9/11 fictions. "An extravagant and wheeling stranger" - encountering the Muslim as the neighbor / Shinjini Basu -- Rewriting the American narrative of Muslim men: Ayad Akhtar's depiction of race, gender, and masculinity / Nalini Iyer -- "There is no Israel for me": je suis Charlie, the ends of the French Republic, and the laicistic contours of Islamophobic dystopia in Michel Houellebecq's Submission / Swayamdipta Das -- Sinhala Budhist nationalism and shrinking space for Muslims in Sri Lanka: the post Tamil Elam War and 9/11 situation / Rajeesh CS -- The making of xenophobia: migrating from hatred to grief in the novels of Mohsin Hamid / Debamitra Kar -- Pax Americana!: American exceptionalism and Salman Rushdie's language of state / Shayeari Dutta -- Reconfiguring the contours of home, belonging, and the rights of conditional citizenship in post 9/11 novels. Imagining citizenship, democracy and belonging in Laila Lalami's Hope and other dangerous pursuits and Ayad Akhtar's Homeland elegies / Sk Sagir Ali -- Globalization, Islamic machine, and "critical localism" in the aftermath of 9/11 / Mosarrap Hossain Khan -- War, terror and migration: Hamid's Exit west as a cosmopolitan novel / Faisal Nazir -- Popular imagination and the ideological representational apparatus of Western media and culture in post 9/11 climate. Tribute in light: memory (re)placed / Pinaki De -- The radical sadness of late-night television: the comedy talk show in the shadow of 9/11 / Sudipto Sanyal and Somnath Basu -- 9/11 and the supervillain crisis: a study of the 'terrorist villain 'and terrorism in select MCU films / Rohan Hassan -- Post 9/11 digital martyrdom - digital ephemera of Ireland and digital protest movement of Bangladesh / Kusumita Datta -- Locating "other" lives and the unmappable registers of precarity in 9/11 novels. Possible lives, impossible times:the tragic queer diasporic Muslim in Ghalib Shiraz Dhalla's The exiles / Anil Pradhan -- "You are my creator, but I am your master": a reading of Frankenstein in Baghdad as a postcolonial Pharmakon / Avijit Basak -- The trauma of familiarity: a very brief overview of British-Muslim writings in the post 9/11 UK / Pinaki Roy.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: War on Terrorism, 2001-2009, in literature; Muslims in literature; Literature and society -- History -- 21st century; September 11 Terrorist Attacks, 2001 -- Influence; Literary criticism; Essays